Effect of Pravastatin Pretreatment and Hypercapnia on Intestinal Microvascular Oxygenation and Blood Flow During Sepsis. Issue 1 (January 2020) - Schulz, Jan; Vollmer, Christian; Truse, Richard; Bauer, Inge; Beck, Christopher; Picker, Olaf; Herminghaus, Anna
ABSTRACT: Introduction: In septic patients, adequate microvascular oxygenation (μHBO2 ) of the intestine is vital for their outcome. Recent studies suggest that statins can ameliorate septic microcirculation in a variety of tissues. However, the effect on intestinal microvascular oxygenation and blood flow is largely unknown. Furthermore, there are indications that statin therapy might not be beneficial in the presence of hypercapnia, as observed in septic acute respiratory distress syndrome (ARDS) patients. Therefore, the present study explores the effect of pravastatin with and without additional moderate acute hypercapnia on intestinal microvascular oxygenation and blood flow in experimental sepsis. Methods: Forty male Wistar rats were randomized into four groups. Half of the animals received 0.2 mg kg −1 pravastatin s.c., the other half received the same volume as vehicle (NaCl 0.9%). After 18 h, colon ascendens stent peritonitis surgery was conducted in all animals to induce sepsis. Twenty-four hours after surgery, baseline was established and the animals were subjected to either 120 min of normocapnic (pCO2 40 ± 6 mm Hg) or moderate hypercapnic (pCO2 72 ± 10 mm Hg) ventilation. Microcirculatory oxygenation (μHBO2 ) and perfusion (μflow) of the colon were continuously recorded using tissue reflectance spectrophotometry and laser Doppler, respectively. Results: In normocapnic septic animals μHBO2 decreased over time (−8.4 ± 8.7%; P  < 0.05 vs. baseline), whereas after pravastatin pretreatment μHBO2 remained constant (−1.9 ± 5.7% vs. baseline). However, in hypercapnic septic animals pretreated with pravastatin μHBO2 declined significantly over time (−8.9 ± 11.8%; P  < 0.05 vs. baseline) and was significantly lower compared with normocapnic pravastatin-pretreated animals. μflow did not change over time in any group. Conclusion: Pravastatin pretreatment ameliorates the intestinal microvascular oxygenation in sepsis and thus seems to prevent intestinal hypoxia. Furthermore, we demonstrated that additional hypercapnia abolishes this effect, indicating why septic ARDS patients might not benefit from pravastatin therapy. Abstract : Supplemental Digital Content is available in the text